Pressure to be Thin from a Religious Source Increases Perceived Pressure to be Thin in Women - Crone, Travis S. (Journal of psychology and theology, 2022)
Pressure to be thin through thin-idealization norms is something that women contend with daily in today’s world. Increased research has explored the effects this pressure can have on attitudes about the self. Religious beliefs and behaviors have been linked to decreased perceived pressure and positive body attitudes and behaviors. However, religious beliefs and behaviors have also been linked to negative outcomes in this area. This study explores the impact of pressure to be thin from a religious source. One hundred fifty-three women were either presented with pressure statements from a religious source, a family/friend source, or read no pressure statements. Women who read religious pressure statements reported more pressure to be thin than those in the control or family/friend pressure conditions.